2018
DOI: 10.1115/1.4041066
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Law Modified to Predict the Pump Head Performance for Different Viscosities Using the Morrison Number

Abstract: The goal of this study is to provide pump users a simple means to predict a pump's performance change due to changing fluid viscosity. During the initial investigation, it has been demonstrated that pump performance can be represented in terms of the head coefficient, flow coefficient, and rotational Reynolds number with the head coefficient data for all viscosities falling on the same curve when presented as a function of ф*Rew−a. Further evaluation of the pump using computational fluid dynamics (CFD) simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The significant vortices occur in the outlet channel of the guide vanes, which decrease the entire stage's efficiency. Therefore, it can be concluded that the guide vanes do not perform their function correctly due to the significant narrowing of the passage channel and the friction of the viscous layers of liquid between themselves [33]. The guide vanes create additional hydraulic losses at increased rotation frequency despite the design methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The significant vortices occur in the outlet channel of the guide vanes, which decrease the entire stage's efficiency. Therefore, it can be concluded that the guide vanes do not perform their function correctly due to the significant narrowing of the passage channel and the friction of the viscous layers of liquid between themselves [33]. The guide vanes create additional hydraulic losses at increased rotation frequency despite the design methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The flow coefficient ϕ, head coefficient ψ, and efficiency η were used to characterize the performance of the LOX turbopump as the nondimensional parameters, and they are defined as follows [49]:…”
Section: Numerical Strategy and Test Verificationmentioning
confidence: 99%
“…The independent variable Φ is replaced by a new independent variable formed by multiplying the flow coefficient by the rotational Reynolds number raised to a power, Φ Patil et al [23] proposed a new method to predict the two-phase flow performance of the terry turbine. The method follows a model previously proposed by authors to characterize the effect of viscosity [24][25][26]. In the case of multiphase pumps working under multiphase flow conditions (liquid + gas), considering the velocity triangle at the impeller blade, the mixture velocity at the inlet depends upon the flow rate, while rotational Reynolds number represents the combined effect of inertial forces, due to rotational speed, and the frictional loss due to the two-phase fluid properties.…”
Section: Application Of Affinity Law For Two-phase Flow Conditionmentioning
confidence: 99%